2002
DOI: 10.1017/s003118200200241x
|View full text |Cite
|
Sign up to set email alerts
|

Fusion to green fluorescent protein improves expression levels of Theileria parva sporozoite surface antigen p67 in insect cells

Abstract: S U M M A R YEast Coast fever (ECF) is a fatal disease of cattle caused by the protozoan parasite Theileria parva. The development of a subunit vaccine, based on the sporozoite-specific surface antigen p67, has been hampered by difficulties in achieving highlevel expression of recombinant p67 in a near-authentic form. Therefore two sets of recombinant baculovirus vectors were constructed. The first set, encoding various regions of p67, produced low levels of the corresponding p67 domains in High Five TM cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…This strategy allowed successful detection with a fluorescent microscope. Improved expression by GFP tagging the N terminus has been observed for other proteins (28). Previous studies showed that ATF6 has a relatively short half-life (ϳ40 min) in HeLa cells.…”
Section: Discussionmentioning
confidence: 97%
“…This strategy allowed successful detection with a fluorescent microscope. Improved expression by GFP tagging the N terminus has been observed for other proteins (28). Previous studies showed that ATF6 has a relatively short half-life (ϳ40 min) in HeLa cells.…”
Section: Discussionmentioning
confidence: 97%
“…Baculovirus expressing TSWV NSs or GFP has been described previously (31,36). Recombinant baculoviruses expressing GRSV NSs and TYRV NSs were constructed using Gateway technology and the Bac-to-Bac system (Invitrogen), following the manufacturers' protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting fragment was cloned into pGEM-T Easy and sequenced. The BamHI-HindIII fragment was recloned in plasmid pFBD-GFP (Kaba et al, 2002) downstream of the AcMNPV polyhedrin (ph) promoter to generate the pFBD-GFP-REPAT1 vector. This plasmid also contains the gfp gene downstream of the AcMNPV p10 promoter to facilitate screening and titration in insect cells.…”
Section: Generation Of Recombinant Baculovirus and Protein Expressionmentioning
confidence: 99%